Analysis of fingerprint patterns and axial triradius digital angles in the Komering population - Sabrina, Siti; Wijaya, Otchi Putri; Mundijo, Trisnawati; Purwoko, Mitayani (Talenta Publisher, 2024)
Some dermatoglyphic components that can be used to analyze a population are fingerprint patterns and Axial Tri-Radius Digital (ATD) angles because they are unique to each ethnic group. This study aimed to determine variations in fingerprint patterns and ATD angles in the Komering population in Palembang. The study of fingerprint patterns and ATD angles was descriptive. The sample size was 43 respondents registered in the Gunung Batu Family Association (IKA GUBA) Komering Ulu Timur in Palembang City. The results showed that the ulnar loop pattern was the most common fingerprint pattern, with 90.4% on the right palmar hand and 85.9% on the left palmar hand. The most minor fingerprint pattern is accidental whorl, which is 0% on the right palmar hand and 1.8% on the left. The 30Â°-45Â° angle dominates the right and left palmar ATD angles (88.4% and 86.0% respectively).